Assessment of knowledge and health behaviors of adolescent’s girls regarding dysmenorrhea and menstrual hygiene at secondary school in Baghdad city (Eurasian Medical Research Periodical, 2022)
A descriptive analytical study was carried out to assess the knowledge and health behaviors of adolescent girls regarding dysmenorrhea and menstrual hygiene at secondary schools in Baghdad city. Probability sample (multi-stage)of (300) adolescents girls age (13-19) years old , and was selected from (23) secondary schools from Directorate of Education in Al-Karkh sector and Al-Russafa sector. Data were collected through the use of a questionnaire form, individual interviewing and self report technique for the period from 8th march to 30th April 2022. Descriptive and inferential statistical procedures were used to analyses the data